Wpływ akcesji do Unii Europejskiej oraz globalizacji na funkcję personalną w przedsiębiorstwach funkcjonujących na terenie Polski (wyniki badań) - Antczak, Zbigniew (The Results of Research on Influence of Accession to the European Union and Globalized Economy on Personnel Function (Human Capital, Human Resources Management) of Enterprises Functioning in Poland, 2008)
The results in the paper come from the author's scientific research and diagnozing personnel function (HC, Human Capital; HRM, Human Resources Management) in selected companies functioning in socio-economic transformation and globalized Polish economy. Research on the selected sample of enterprises functioning in Polish conditions lets me conclude (synthetic diagnosis: quality conclusion with restricted range of generalization) that the lack of stable development perspectives and organization-capital base (e.g. a capital group, a home organization or a strategic investor) in the presence of variability and uncertainty of environment - regardless of business - translates in destructive and impoverishing way into the realization of personal function and generating human capital in small and medium enterprises. This phenomenon is often increased by low creative-management qualifications of apart of managers who run a company. Such a situation of an enterprise functioning in Polish realities generates among others a lot of demands from which stability of economic situation (among others from the side of the state) and improvement of a financial-banking system functioning come to the front. The next one is to improve creative-management qualifications of management personnel. The accession to the European Union which is combined with generation personnel replacement may partially contribute to a solution to these problems. Big organizations of leading knowledge societies (global background), generating HC, consolidate their competitive advantage and additionally profit because of that. Valuable human capital serve them among others to build a strategic advantage of an enterprise (both in global and local-regional dimension), to outdistance competition and to profit more. It should be expected that Polish managers, either working in corporate enterprises or competing with them and observing solutions which are used there, learn to function in the realities of global knowledge society. Therefore, they will assimilate and adopt concept of human capital to conditions they will have to take actions in.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 194-207